Bank governance and performance: a survey of the literature - Fernandes, Catarina (2019)
This paper seeks to review the theoretical and empirical literature on the relationship between bank governance and performance, providing a comprehensive understanding of the existing research and offering guidance for investors and regulators on the major points of consensus and disagreement among researchers on this issue. Although the question of what determines the levels of firms’ performance, with special emphasis on the role of the corporate governance, has long been the subject of substantial academic research, it gained increased attention in the banking industry in the last decade due to a series of financial scandals and, more recently, to the global financial crisis. In fact, in the wake of the 2007–2008 financial crisis, bank corporate governance mechanisms received heightened attention, accompanied by the renewed interest in the degree of effectiveness of such mechanisms, and their impact on performance. Given the vast number of influences on corporate performance, such as the numerous characteristics of the board of directors, there is an abundant literature on the determinants of performance. Thus, this paper tries to bring together this diverse body of knowledge into a coherent whole. Banks have unique attributes that interfere with the way in which the usual corporate governance mechanisms work. Thus, the main differences between banks and non-financial firms, which justify that some of the regularities found in the literature on the relationship between a set of corporate governance mechanisms and performance do not hold for banks, are also analysed. Then, we extensively review the literature on the board of directors and its impact on performance in the financial crisis and non-financial crisis periods. Finally, we also survey the (very) scarce research on the relationship between board characteristics and bank failures.